Pelatihan Pembuatan Sabun Cair Ramah Lingkungan Untuk Peningkatan Ekonomi Kreatif Jemaat - Sri Hartini; Dewi Kurnianingsih Arum Kusumahastuti; Margareta Novian Cahyanti; Sarawinda Hutagalung; Fajar Yusuf Arfiyan; Putra Kaysha Qodiriy; Olivier Surya Simonet; Fidelis Tertius Aluh Christyawardana; Firman Emmanuel Declarantius Parulian (CV. ITTC INDONESIA, 2026)
The main problems faced by the congregation are limited entrepreneurial skills and the underutilization of creative economic opportunities based on environmentally friendly products, resulting in low additional household income. This community service program aims to improve the knowledge, skills, and economic independence of congregation members through training in the production of environmentally friendly liquid soap with market value. The program was conducted using a participatory training method, including counseling, demonstrations, and hands-on practice. Qualitative descriptive analysis was applied by comparing participants’ knowledge and skills before and after the training and evaluating the products produced. The results show an increase in participants’ understanding of materials and production processes, as well as their ability to produce liquid soap suitable for use and commercialization. Overall, the training has strong potential to support creative economic development and sustainably improve the welfare of the congregation. This initiative encourages long-term entrepreneurship and environmental awareness among participants.